2022
DOI: 10.1371/journal.pone.0267156
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between SERCA, 4E-BP, and eIF4E in the Drosophila heart

Abstract: Appropriate cardiac performance depends on a tightly controlled handling of Ca2+ in a broad range of species, from invertebrates to mammals. The role of the Ca2+ ATPase, SERCA, in Ca2+ handling is pivotal, and its activity is regulated, inter alia, by interacting with distinct proteins. Herein, we give evidence that 4E binding protein (4E-BP) is a novel regulator of SERCA activity in Drosophila melanogaster during cardiac function. Flies over-expressing 4E-BP showed improved cardiac performance in young indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Interestingly, all these genes are known FOXO targets (Brankatschk et al, 2014), which implicates the involvement of this transcription factor in the mediation of IMPL2 effects. This notion is supported by the expression of two commonly used FOXO readouts (Thor, 4EBP; eukaryotic translation initiation factor 4E1, eIF4E1; Santalla et al, 2022), showing analogous expression patterns with respect to infection and Mϕ-ImpL2 manipulations (Fig 3F). Consistent with metabolic effects attributed to Mϕ-ImpL2 manipulations, identical metabolic effect has been achieved also by using an alternative ImpL2 RNAi fly line .…”
Section: Macrophage-derived Impl2 Directs the Infection-induced Mobil...mentioning
confidence: 61%
“…Interestingly, all these genes are known FOXO targets (Brankatschk et al, 2014), which implicates the involvement of this transcription factor in the mediation of IMPL2 effects. This notion is supported by the expression of two commonly used FOXO readouts (Thor, 4EBP; eukaryotic translation initiation factor 4E1, eIF4E1; Santalla et al, 2022), showing analogous expression patterns with respect to infection and Mϕ-ImpL2 manipulations (Fig 3F). Consistent with metabolic effects attributed to Mϕ-ImpL2 manipulations, identical metabolic effect has been achieved also by using an alternative ImpL2 RNAi fly line .…”
Section: Macrophage-derived Impl2 Directs the Infection-induced Mobil...mentioning
confidence: 61%
“…Indeed, eIF4E‐4 mRNA and protein are present in the cardiac tissue of adult flies. The specific identification of eIF4E‐4 in the heart supports the notion that the interaction of SERCA with elF4E‐4 might underlie the cardiac effects observed in 4E‐BP‐over‐expressing flies associated with incremented SERCA activity (Santalla et al ., 2022). Thus, eIF4E‐4 might be a negative regulator of SERCA.…”
Section: Eif4e In Drosophilamentioning
confidence: 99%
“…In mammals and invertebrates, heart performance relies on a tightly regulated handling of Ca 2+ , a process in which the ATPase sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) plays a pivotal role (Gambardella et al, 2018). Recent evidence showed that SERCA is regulated in the Drosophila heart by 4E-BP during cardiac function (Santalla et al, 2022) (Fig. 6C).…”
Section: Eif4e In Drosophilamentioning
confidence: 99%